2022
DOI: 10.3390/jcm11164688
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Neutrophil-to-Lymphocyte Ratio in Patients with COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has had a major impact on global health, continuing to put strain on healthcare systems and disrupting socioeconomic life [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It has been reported that an elevated NLR is often observed in conditions that involve tissue damage and activate the systemic inflammatory response, such as bacterial and fungal infections, sepsis, acute stroke, atherosclerosis, myocardial infarction, severe trauma, and cancer [27,28]. Recently, studies revealed that NLR can predict clinical outcomes and plays as an easyto-obtain biomarker to evaluate severity for Covid-19 patients [29,30]. A multicenter retrospective cohort study from France investigated the prognostic value of the NLR for disease severity and mortality in 1035 COVID-19 patients [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an elevated NLR is often observed in conditions that involve tissue damage and activate the systemic inflammatory response, such as bacterial and fungal infections, sepsis, acute stroke, atherosclerosis, myocardial infarction, severe trauma, and cancer [27,28]. Recently, studies revealed that NLR can predict clinical outcomes and plays as an easyto-obtain biomarker to evaluate severity for Covid-19 patients [29,30]. A multicenter retrospective cohort study from France investigated the prognostic value of the NLR for disease severity and mortality in 1035 COVID-19 patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…The PCR results contains nucleocapsid protein (N) gene and open reading frame (ORF) gene. N gene Ct value was 30 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and ORF gene was 33 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).The median of total lung volume was 3088ml (1055-3809ml), GGO pattern was 833ml (392-1047ml) and its corresponding ratio to total lung was 30.3% (8.1%-40.3%); while the consolidation pattern was 186ml (63-316ml), the ratio was 7.2% (1.7%-11.4%); the affected lung was 1045ml (482-1359ml), and the ratio was 39% (10%-55%). ROC test results showed the area under the curve (AUC) for N gene, ORF gene, leukomonocyte count, N gene + leukomonocyte count, and ORF gene + leukomonocyte count were 0.562, 0.567, 0.703, and 0.582, respectively when adjusted with age, gender, and C reaction protein level (p <0.05 results are shown in Fig.…”
Section: (Table 1 Set Here)mentioning
confidence: 99%
“…In total, 13 studies have been published this year alone (2022) that independently showed that higher NLR in COVID-19 patients entering the hospital was a strong predictor of in-hospital worsening or death [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Chart review showed this to be the case also at our ICU, independently of whether dapsone was given or not.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that hematological parameters such as white blood cell count (WBC), lymphocyte count, neutrophil count, eosinophil count, platelet count, hemoglobin, neutrophil-lymphocyte ratio (NLR), C-reactive protein (CRP), platelet-lymphocyte ratio (PLR), Lymphocyte-to-monocyte ratio (LMR) and C-reactive protein-to-lymphocyte ratio (CLR) are helpful in stratifying the severity of patients with COVID-19 [11][12][13][14]. However, their predictive value has not been explicitly evaluated among those severely ill.…”
Section: Introductionmentioning
confidence: 99%